A transmission of beta herding during subprime crisis in Taiwan's market: DCC-MIDAS approach - Yi-Chang Chen; Hung-Che Wu; Yuanyuan Zhang; Shih-Ming Kuo (International Journal of Financial Studies, 2021)
The aim of this study is to investigate the herding of beta transmission between return and volatility. We have used the dynamic conditional correlation model with the mixed-data sampling (DCC-MIDAS) model for the analysis. The evidence demonstrates that herding is a key transmitter in Taiwan's stock market. The significant estimation of DCC-MIDAS explains that the herding phenomenon is highly dynamic and time-varying in herding behavior. By means of time-varying beta of herding based on our rolling forecasting method and robustness check of the Markov-switching regression approach using four types of portfolios, the evidence indicates that there are conditional correlations between betas and herding. In addition, it also reveals that herding forms in Taiwan's markets during the subprime crisis period.
Keywords: 330; DCC-MIDAS; herding; Markov switching; subprime crisis; time-varying